Implementasi Kurikulum 2013 Pada Mata Pelajaran Geografi di Sma Negeri SeKabupaten Pemalang - Hermawan, Arief Yulianto; Sriyanto, Sriyanto (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2019)
The purpose of this study was to (1) find out the learning planning in the 2013 curriculum implementation (2) find out the implementation of learning in the 2013 curriculum implementation (3) find out the assessment system in the 2013 curriculum (4) analyze the driving and inhibiting factors in the 2013 curriculum implementation. The purposive sampling technique was used to take a sample of 10 geography teachers from 10 schools, where each school was taken by 1 geography teacher who had participated in the training and implemented the 2013 curriculum during learning. Data collection uses questionnaires, observation, interviews and documentation. The results of the study show that (1) the geography teacher's learning planning falls into very good criteria (2) the implementation of learning by geography teachers in which 7 schools fall into very good criteria and 3 schools fall into sufficient criteria (3) teacher assessment geography falls into very good criteria (4) there are still some obstacles faced by geography teachers in implementing the 2013 curriculum. Tujuan penelitian ini adalah untuk (1) mengetahui perencanaan pembelajaran dalam implementasi kurikulum 2013 (2) mengetahui pelaksanaan pembelajaran dalam implementasi kurikulum 2013 (3) mengetahui sistem penilaian dalam kurikulum 2013 (4) menganalisis faktor-faktor pendorong dan penghambat dalam implementasi kurikulum 2013. Teknik purposive sampling digunakan untuk mengambil sampel sebanyak 10 guru geografi dari 10 sekolah, dimana setiap sekolah diambil 1 guru geografi yang sudah ikut pelatihan dan mengimplementasikan kurikulum 2013 pada saat pembelajaran. Pengumpulan data menggunakan quesioner, observasi, wawancara dan dokumentasi. Hasil penelitian menunjukan bahwa (1) perencanaan pembelajaran oleh guru geografi masuk ke dalam kriteria sangat baik (2) pelaksanaan pembelajaran oleh guru geografi dimana 7 sekolah masuk ke dalam kriteria sangat baik dan 3 sekolah masuk ke dalam kriteria cukup (3) penilaian pembelajaran oleh guru geografi masuk ke dalam kriteria sangat baik (4) masih terdapat beberapa kendala yang dihadapi oleh guru geografi dalam mengimplementasikan kurikulum 2013.